Fibre optic sensor enabled containment zone - Suman, Preetam (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There are many sensitive areas like country borders, banks, forests, army cantonments, jails which requires continuous monitoring and surveillance. Intruders and illegal elements try to break the security and enter into these areas. In the same way there is another sensitive zone called containment zone required protection to prevent spread of viruses like corona. Every country has established their own protocols to maintain containment zone. Security officials monitored the sensitive areas but still it was not safe enough. In this case there is need of an invisible security mechanism which can be applicable in maintaining movements in containment zones. It will be very important to detect any movement in the sensitive area. Therefore, this paper provides a solution to protect sensitive zones. The solution consists of optical fibre sensor along with reporting and alarming system. The design and implementation is explained in the paper along with results. The proposed solution can be implemented to secure zone for multiple applications.